1985
DOI: 10.1002/j.1460-2075.1985.tb04083.x
|View full text |Cite
|
Sign up to set email alerts
|

T4 phage gene uvsX product catalyzes homologous DNA pairing.

Abstract: Gene uvsX of phage T4 controls genetic recombination and the repair of DNA damage. We have recently purified the gene product, and here describe its properties. The protein has a single‐stranded DNA‐dependent ATPase activity. It binds efficiently to single‐ and double‐stranded DNAs at 0 degrees C in a cooperative manner. At 30 degree C the double‐stranded DNA‐protein complex was stable, but the single‐stranded DNA‐protein complex dissociated rapidly. The instability of the latter complex was reduced by ATP. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 41 publications
3
49
0
Order By: Relevance
“…It catalyzes the linear, duplex by single-strand circle strand-exchange reaction by pairing the 3'-homologous end of the linear duplex strand with the single-stranded circle followed by extension of the hybrid region toward the 5' end of the linear duplex strand (3'-to-5' direction) whereas all presently known eukaryotic proteins catalyze this reaction in the 5'-to-3' direction (22,23,(27)(28)(29)(30). Also, it requires a high protein/singlestranded DNA molar ratio approaching that required by the RecA and UvsX proteins, and the reaction shows a high degree of cooperativity (12,(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It catalyzes the linear, duplex by single-strand circle strand-exchange reaction by pairing the 3'-homologous end of the linear duplex strand with the single-stranded circle followed by extension of the hybrid region toward the 5' end of the linear duplex strand (3'-to-5' direction) whereas all presently known eukaryotic proteins catalyze this reaction in the 5'-to-3' direction (22,23,(27)(28)(29)(30). Also, it requires a high protein/singlestranded DNA molar ratio approaching that required by the RecA and UvsX proteins, and the reaction shows a high degree of cooperativity (12,(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Stable joint formation appears to initiate in both the 3'-to-5' and 5'-to-3' directions; however, extensive heteroduplex formation is polar and proceeds in the 3'-to-5' direction (22,23). The bacteriophage T4 UvsX protein appears to catalyze strandexchange reactions in a similar fashion to the RecA protein (24)(25)(26)(27),…”
mentioning
confidence: 99%
“…Both ADP-AlF 4 Ϫ and ATP-␥-S are being used in this case as analogs for ATP, but it can clearly be seen that the filament structure depends on which analog is being used. Numerous studies have shown that aluminum fluoride can serve as a very good non-hydrolyzable analog for ATP (28), whereas it has been shown that ATP-␥-S is slowly hydrolyzed by proteins such as RecA (29)(30)(31). The smaller pitch filaments, resembling the ''collapsed'' state of the RecA filament formed in the absence of ATP (25), have previously been seen with hRad51 protein on ssDNA when ATP-␥-S was used as a cofactor (23).…”
Section: N-terminal Domain Of Rad51mentioning
confidence: 99%
“…Proteins in this family include UvsX of a bacterial virus (Escherichia coli phage T4: ref. 16), RecA of various bacteria, RadA of archaea, and the Rad51-family proteins found in various eukaryotes from yeast to human beings (refs. 17 and 18, and see ref.…”
Section: Homologous Recombinationmentioning
confidence: 99%